Quantitative risk assessment and dispersion modelling using ALOHA for chlorine gas handling facility / Uvaraja Kusala - Uvaraja , Kusala (2020)
Malay-Sino Chemical Industries Sdn Bhd (Lahat) is a chlor-alkali industry consist of Emergency Chlorine Gas Handling Facility (ECGHF) which have the tendency to affect the plant workers and nearby residential area in the event of accidental chlorine gas release. HAZOP tool with risk assessment was used to identify the hazard and quantifying the hazards in order to prioritize the recommendations at the ECGHF. Possible incident scenario was selected from the HAZOP outcome which was the chlorine gas release from the stack due to scrubbing flow failure. The consequences of the released chlorine gas to the atmosphere was simulated by using ALOHA Vr 5.4.7 software where heavy gas dispersion model was selected which identifies the impacted area along with the concentration of the chlorine gas for TWO (2) wind direction (East and West) with other atmospheric conditions remain the same. The maximum emission rate was selected which is at 199kg/hr. Based on the findings from the modelling for both wind directions, the toxic threat zones and distances along with the concentration of chlorine plume remain same for both wind directions which is at 0.5ppm (1,100m), 2ppm (537m), and 20ppm (161m) and represented in Yellow, Orange, and Red lines and the threat zones are of 1,100m maximum radius. The probit analysis indicated there’s no human fatality percentage predicted due to the chlorine gas exposure. The map from google satellite was used to identify the impacted residential areas in which the areas are Bukit Merah Village, Taman Menglembu Impiana Adril, and Taman Pasir Wang. Recommendations were proposed to eliminate the chlorine gas release from the ECGHF thus increasing the safety and reliability of operation.